Viewpoints of Intercultural Competence Development in English Language Teaching / Learning Classroom - Kriaučiūnienė, Roma; Šiugždinienė, Auksė (Verbum, 2010)
The article presents an analysis of viewpoints on the development of intercultural competence in the English language teaching/learning classroom. Intercultural competence, acknowledged as the key component of foreign language studies, increases the need to adapt teaching methods and materials to raise learners’ cultural awareness. The following research problem is formulated: how schoolchildren’s intercultural competence is developed at schools during English language classes and what the preconditions of its improvement are. Based on the survey carried out at secondary schools and gymnasiums, the article presents the findings on the ninth and tenth formers’ viewpoints regarding the extent to which cultural activities are incorporated into their English language classroom. The respondents’ answers indicated that the present practices for the development of intercultural competence in the English language classroom are not sufficient. A conclusion is made that the English language teaching/ learning process should be more purposefully aimed at developing all the dimensions of learners’ intercultural competence.